Glycolysis Aids in Human Lens Epithelial Cells’ Adaptation to Hypoxia - Yuxin Huang; Xiyuan Ping; Yilei Cui; Hao Yang; Jing Bao; Qichuan Yin; Hailaiti Ailifeire; Xingchao Shentu (Antioxidants, 2023)
Hypoxic environments are known to trigger pathological damage in multiple cellular subtypes. Interestingly, the lens is a naturally hypoxic tissue, with glycolysis serving as its main source of energy. Hypoxia is essential for maintaining the long-term transparency of the lens in addition to avoiding nuclear cataracts. Herein, we explore the complex mechanisms by which lens epithelial cells adapt to hypoxic conditions while maintaining their normal growth and metabolic activity. Our data show that the glycolysis pathway is significantly upregulated during human lens epithelial (HLE) cells exposure to hypoxia. The inhibition of glycolysis under hypoxic conditions incited endoplasmic reticulum (ER) stress and reactive oxygen species (ROS) production in HLE cells, leading to cellular apoptosis. After ATP was replenished, the damage to the cells was not completely recovered, and ER stress, ROS production, and cell apoptosis still occurred. These results suggest that glycolysis not only performs energy metabolism in the process of HLE cells adapting to hypoxia, but also helps them continuously resist cell apoptosis caused by ER stress and ROS production. Furthermore, our proteomic atlas provides possible rescue mechanisms for cellular damage caused by hypoxia.